Diabetes risk scores for Hispanics living in the United States: A systematic review. (August 2018) - Juarez, Lucia D.; Gonzalez, Jeffrey S.; Agne, April A.; Kulczycki, Andrzej; Pavela, Gregory; Carson, April P.; Shelley, John P.; Cherrington, Andrea L.
Highlights: First systematic review of risk scores for undiagnosed diabetes applicable to Hispanics. Few risk scores for undiagnosed diabetes are validated in Hispanic populations. Risk scores validated for Hispanics lacked risk factors specific to these populations. Abstract: Aim: Undiagnosed diabetes is more prevalent among racial/ethnic minorities in the United States (U.S.). Despite the proliferation of risk scores, few have been validated in Hispanics populations. The aim of this study is to systematically review published studies that developed risk scores to identify undiagnosed Type 2 Diabetes Mellitus based on self-reported information that were validated for Hispanics in the U.S. Methods: The search included PubMed, EMBASE, Cochrane and CINAHL from inception to 2016 without language restrictions. Risk scores whose main outcome was undiagnosed Type 2 diabetes reporting performance measures for Hispanics were included. Results: We identified three studies that developed and validated risk scores for undiagnosed diabetes based on questionnaire data. Two studies were conducted in Latin America and one in the U.S. All three studies reported adequate performance (area under the receiving curve (AUC) range between 0.68 and 0.78). The study conducted in the U.S. reported a higher sensitivity of their risk score for Hispanics than whites. The limited number of studies, small size and heterogeneity of the combined cohorts provide limited evidence of the validity of risk scores for Hispanics. Conclusions: Efforts to develop and validate risk prediction models in Hispanic populations in the U.S are needed, particularly given the diversity of this fast growing population. Healthcare professionals should be aware of the limitations of applying risk scores developed for the general population on Hispanics.